2017
DOI: 10.1044/2017_jslhr-l-16-0093
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Coverbal Gesture Use in Oral Discourse Among Speakers With Fluent and Nonfluent Aphasia

Abstract: Purpose: Coverbal gesture use, which is affected by the presence and degree of aphasia, can be culturally specific. The purpose of this study was to compare gesture use among Cantonese-speaking individuals: 23 neurologically healthy speakers, 23 speakers with fluent aphasia, and 21 speakers with nonfluent aphasia. Method: Multimedia data of discourse samples from these speakers were extracted from the Cantonese AphasiaBank. Gestures were independently annotated on their forms and functions to determine how ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…To examine the relationship between co-verbal gesture use and lexical retrieval more rigorously among unimpaired speakers and PWA, the current study adopted a method different from Kong, Law, Wat, et al (2015) and Kong et al (2017). All instances of WFD in controls and PWA were first identified, before examining if each incident co-occurred with the speakers’ employment of a gesture.…”
Section: Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the relationship between co-verbal gesture use and lexical retrieval more rigorously among unimpaired speakers and PWA, the current study adopted a method different from Kong, Law, Wat, et al (2015) and Kong et al (2017). All instances of WFD in controls and PWA were first identified, before examining if each incident co-occurred with the speakers’ employment of a gesture.…”
Section: Aimsmentioning
confidence: 99%
“…It was observed that higher use of gestures in the PWA group was associated with improved lexical retrieval. A follow-up study by Kong, Law, and Chak (2017) compared co-verbal gesture employment among 23 fluent PWA, 21 non-fluent PWA, and 23 controls. The results revealed an association between improved WFD and use of non-content-carrying gestures among PWA (unlike the use of content-carrying gestures in controls during WFD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gesture production also seems to vary by type of aphasia and on the dimension of fluency; Cicone et al (1979) found that gesture form parallels verbal output where people with non-fluent aphasia produced fewer but clear and informative gestures, and people with fluent aphasia produced frequent but vague gestures. In contrast, other studies have found that people with non-fluent aphasia gesture at higher rates than those with fluent aphasia ( Kong et al, 2017 ). In a story retell task, people with non-fluent Broca’s aphasia produced almost twice as many gestures per 100 words as people with fluent Wernicke’s aphasia, and they also differed by gesture type; people with Broca’s aphasia were more likely to produce meaningful gestures such as iconic gestures whereas those with Wernicke’s aphasia produced more beat and metaphoric, or abstract, gestures ( Sekine et al, 2013 ).…”
Section: Gesture In Neurogenic Communication Disordersmentioning
confidence: 66%
“…Supporting this view, studies report that people with aphasia (PWA) use gestures at a higher frequency than healthy adults (e.g., Feyereisen, 1983;LeMay, David, & Thomas, 1988). Although different patholinguistic profiles yielded differential patterns of gesture use by PWA (e.g., Hadar, Wenkert-Olenik, Krauss, & Soroker, 1998;Kronke, Kraft, Regenbrecht, & Obrig, 2013;Preisig et al, 2018;Rose, 2006), more severe forms of aphasia were generally associated with greater use of spontaneous co-speech gestures (Carlomagno & Cristilli, 2006;Kong, Law & Chak, 2017). However, many of these studies focused on general language use and investigated the integrity of gestures in speech by employing semi-structured interviews, free conversations, and narrating stories (e.g., Dipper, Cocks, Rowe, & Morgan, 2011;Lausberg, Davis, & Rothenhäuser, 2000;Rose & Douglas, 2003).…”
Section: Introductionmentioning
confidence: 99%